Presenting a Detailed Model for the Distribution of Endowment Papers in Iran - Abouzar Sorosh (تحقیقات مالی اسلامی (پیوسته), 2011)
As the most perfect divine religion, the holy Islam contains comprehensively complete programs leading human-being to prosperity and salvation. One of the recommendations highly emphasized in the religion of Islam is charitable endowment. Though being not compulsory, endowment is highly advised in the religion and has a well-deserved role in elevating our souls and providing spirituality for the whole community. Many people are interested in giving endowments; however, it is not possible for all to do so, especially when the endowed object is a building, school, etc, because such things require the person to undergo a huge cost, which is not possible for everybody. Using the suggestions proposed regarding the expansion and diversity of financial tools, the present article is intended to offer a model that solves the above-mentioned problem. In addition to absorbing small capital of individuals, the distribution of endowment papers will also lead to the promotion of endowment culture. Such papers are non-for-profit, and the owner, after earning the property, finds the possibility to endow it. Hence, in addition to examining the foundations effective on the process of distributing endowment papers, the present essay is also intended to present the financial model related to such papers.